Efectiveness Of Carica papaya Seeds Ethanol Extract With Metronidazole Against Porphyromonas gingivalis In Antibacterial And Antibiofilm Activity - Thebez, Vanessa Angela; Soesanto, Sheila; Natassya, Priska (JURNAL BIOSAINS, 2025)
Introduction: Porphyromonas gingivalis promotes the growth of periodontal biofilm. Metronidazole is one of the adjunctive therapies for periodontitis. The combination of metronidazole with natural products such as Carica papaya seeds ethanolic extract, which has proven to have antibacterial effects is expected to reduce the side effects caused by metronidazole. Objective: To determine the antibacterial and antibiofilm effects of C. papaya seeds ethanolic extract combined with metronidazole against P. gingivalis. Methods: In vitro laboratory experiment using post-test only control group design. The sample used were 100% C. papaya seeds ethanolic extract, combination of 1000 µg/mL metronidazole with extract 3.125%, 6.25%, 12.5%, 25%, 50%, and 100%, 1000 µg/mL and 2000 µg/mL metronidazole as positive control, and distilled water as negative control. Antibacterial test was performed using plate count method and antibiofilm using microtiter plate biofilm assay method. Results: Carica papaya seeds ethanolic extract alone showed effective antibacterial and antibiofilm effects against P. gingivalis. The combination of 1000 µg/mL metronidazole with extract 6.25% to 100% showed an antibacterial effect equivalent to 2000 µg/mL metronidazole. The combination of 1000 µg/mL metronidazole with 100% extract showed antibiofilm effects in 1, 3, and 24 hours time incubation. The combination of extract and 1000 µg/mL metronidazole demonstrated the best antibiofilm effect during the biofilm maturation phase. Conclusion: The combination of 1000 µg/mL metronidazole with ethanol extract of C. papaya seeds exhibited antibacterial and antibiofilm effects against P. gingivalis.